Feasibility and performance analysis of hybrid ground source heat pump systems in fourteen cities. (1st November 2021) - Weeratunge, Hansani; Aditya, Gregorius Riyan; Dunstall, Simon; de Hoog, Julian; Narsilio, Guillermo; Halgamuge, Saman
Abstract: Ground source heat pump systems (GSHP) for residential building heating, cooling, and hot water are highly energy efficient but capital intensive when sized for peak demands. The use of supplemental sources of energy with GSHP systems enables improved life-cycle economics through the reduction in the size and cost of the GSHP components. This paper investigates the life-cycle economics of hybrid solar-assisted ground source heat pump systems (SAGSHP) using simulations validated from field data. The economics and optimal sizing of SAGSHP systems for heating dominant climates in four locations in Australia and ten locations elsewhere are evaluated in order to explore the suitability and relative merits of SAGSHP systems in a range of heating dominant climates. In locations having high or moderate levels of solar irradiation, high electricity prices, and high or moderate gas prices, SAGSHP systems are shown to have the lowest life cycle cost amongst alternatives, with predicted savings of up to 30%. Highlights: A comprehensive investigation of the design and performance of hybrid GHSPs. A comparison of hybrid GSHPs and conventional systems on cost and CO2 emissions. Effects of local climatic and economic conditions are evaluated for 14 global cities. Hybrid GSHPs have shown to be the most economical system for 10 out of 14 locations. Local energy price is a key factor that influences the feasibility of hybrid GSHPs.